Sharp Pulses in a Semiconductor Laser Array Subject to Optical Feedback and Transverse Coupling - Scranton, Greggory; Spitz, Olivier; Crespo, Matthew; Berrill, Mark; Braiman, Yehuda (2024 IEEE 29th International Semiconductor Laser Conference (ISLC), 2024)
We report on sharp pulses in an array of semiconductor lasers that are coupled via an external cavity. Analysis of the combined laser fields shows that a major drop of intensity occurs before pulses are triggered. Pulsing is thus preceded by a temporal destructive interference.